2010
DOI: 10.1179/016164109x12537002794200
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture attenuates extracellular glutamate level in global ischemia model of rat

Abstract: This result suggests that the effect of acupuncture might be closely associated with modulation of the brain glutamate release in the ischemic condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…9 At present, EA is widely used experimentally and clinically to treat disorders of the nervous system, such as stroke. [10][11][12][13][14][15] However, there are few studies and reports on the influence of EA after TBI, especially regarding its effect on the regional blood flow and neuronal TGIF expression involved in cellular apoptosis during the acute stage.…”
Section: Introductionmentioning
confidence: 99%
“…9 At present, EA is widely used experimentally and clinically to treat disorders of the nervous system, such as stroke. [10][11][12][13][14][15] However, there are few studies and reports on the influence of EA after TBI, especially regarding its effect on the regional blood flow and neuronal TGIF expression involved in cellular apoptosis during the acute stage.…”
Section: Introductionmentioning
confidence: 99%
“…As evidences given by recently extensive reports, the beneficial effects of acupuncture on brain ischemic damage in vivo or in vitro mainly focus on microcirculation [24], anti-apoptotic [25], anti-inflammation [26], neuron protection [27], brain metabolism [28]. Our previous studies indicated that acupuncture combined with basic modern medicine treatment showed a great effect on stroke patients' self-care ability and quality of life in clinic trial [12], and the underlying mechanism may be associated with improving cerebral haemodynamics and neuron protective effect under a special stimulated parameter on a special acupionts revealed by animal researches [13, 29, 30].…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al reported that acupuncture can attenuate extracellular glutamate levels in a global ischemia model in rat. In the study, the authors found that acupuncture at GB34 and GB39 significantly suppressed glutamate function compared to control animals [22]. Later, Kim et al demonstrated that acupuncture at HT7 can inhibit methamphetamine-induced behaviors, dopamine release and hyperthermia in the nucleus accumbens through the group II metabotropic glutamate receptors [23].…”
Section: Evidence From Electrochemical Studiesmentioning
confidence: 96%